“Anti-soviet” activities of Juozas Žiugžda in 1951–1955 in the ‘methodologists’’ agency case - Selenis, Valdas (Genocidas ir rezistencija, 2024)
According to the 1951–1955 MGB (Ministry for State Security) case entitled ‘Methodologists’, which is stored in the Lithuanian Special Archives, agency statements, and records of interrogations, this article reveals how Juozas Žiugžda, a typical Soviet historian, fell into the hands of Soviet security. As a member and vice-president of the Academy of Science of the Lithuanian SSR, the minister of education, director of the Institute of History, and head of the Department of the History of the Lithuanian SSR and the Department of the History of the USSR of Vilnius University, Žiugžda was obligated to supervise the system of education and the study of history. He was made to do so due to the ‘inappropriateness’ of his background. The article provides the records of Žiugžda prepared by special agents, reviews his ‘harmful’ activities at the Ministry of Education of the Lithuanian SSR and the Institute of History, and provides information about the employees of the ministry who were also charged in the case. The analysis of the material of the case shows that Žiugžda was charged with being a member of the Social Democratic and National parties and taking part in anti-Soviet activities and publications at the time of independent Lithuania. Incriminating evidence included his ‘harmful’ activities in the system of education of the Lithuanian SSR: the slow reform of the network of secondary schools according to the Soviet model, approval of Lithuanian literature textbooks that were ‘inappropriately’ prepared, and ‘harmful’ activities at the Institute of History of the Academy of Science of the Lithuanian SSR—the delay of the issue of a textbook about the history of the Lithuanian SSR. The article concludes that the investigation of the ‘anti-Soviet’ activities of Žiugžda was not deliberately pre-planned, because at the beginning information was collected about the activities of Petras Mikutaitis, an employee of the Ministry of Education, and his associates, who were deemed to have been possibly involved in ‘criminal activities’. Žiugžda was included in the investigation as the head of the system of education responsible for his subordinates. Additional ‘evidence’ against him appeared as a result of the conflict between him and two employees at the Institute of History, Stasys Matulaitis and Juozas Jurginis, when Žiugžda dismissed them. At the conclusion of the case, the information collected about Žiugžda was acknowledged to be of minor importance and such favourable conclusion was influenced by the leadership of the Central Committee of the Communist Party of Lithuania and particularly Antanas Sniečkus, the secretary general of the party.